Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi: (Studi Kasus : PT Sinergi Adimitra Jaya) - Angelina Latuharhary, Rossy; Alamsyah, Muhammad Riyan; Agustian, Sukri; Wiyatno, Tri Ngudi; Josef Anis, Billy (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
In an increasingly competitive business environment, employee performance is a crucial factor in determining the sustainability and competitiveness of a company. Employee performance is influenced by several factors, such as leadership style and work environment. This study focuses on PT Sinergi Adimitra Jaya, a manufacturing company specializing in the production of baby and adult diapers, to analyze the influence of these factors on employee performance with job satisfaction as a mediating variable. The research approach used in this study is a quantitative approach. Data collection was carried out by survey using questionnaires distributed to 102 employees. The sampling technique used saturated sampling. The data collected were then analyzed using SEM-PLS (Structural Equation Modeling-Partial Least Squares) through SMART PLS 4.0 software. The analysis includes outer and inner models to assess validity, reliability, and relationships between variables. The results of the study indicate that leadership style has a positive and significant influence on employee performance. However, job satisfaction does not significantly mediate the relationship. Conversely, the work environment does not have a significant direct influence on employee performance. Job satisfaction does not mediate its influence. The evaluation of the model resulted that leadership style and work environment explained 38.1% of the variability in job satisfaction, while 31.2% of the variability in employee performance was explained by leadership style, work environment, and job satisfaction.